2004
DOI: 10.1007/s00134-004-2231-7
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic status, cough, secretions and extubation outcomes

Abstract: These simple, reproducible methods may provide a clinically useful approach to guiding the extubation of patients who have passed a SBT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
202
4
17

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 283 publications
(241 citation statements)
references
References 8 publications
13
202
4
17
Order By: Relevance
“…Further, other investigators have reported that the absolute amount of tracheal secretions and inadequate cough response increases the risk of extubation failure in patients who no longer appear to need mechanical ventilation. 6,15,16 Consistent with a previous report, 11 another risk factor for extubation failure was the number of previously failed SBTs, which suggests that, despite a pattern of improvement over time, some patients with more difficult weaning may not have achieved complete resolution of acute respiratory failure and may be more likely to require reintubation. 17 Frutos-Vivar et al also reported that positive fluid balance in the previous 24 hours was a significant predictor of extubation failure.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Further, other investigators have reported that the absolute amount of tracheal secretions and inadequate cough response increases the risk of extubation failure in patients who no longer appear to need mechanical ventilation. 6,15,16 Consistent with a previous report, 11 another risk factor for extubation failure was the number of previously failed SBTs, which suggests that, despite a pattern of improvement over time, some patients with more difficult weaning may not have achieved complete resolution of acute respiratory failure and may be more likely to require reintubation. 17 Frutos-Vivar et al also reported that positive fluid balance in the previous 24 hours was a significant predictor of extubation failure.…”
Section: Discussionsupporting
confidence: 84%
“…22 Salam and colleagues reported that subjects unable to complete 4 task commands (open eyes, follow with eyes, grasp hand, and stick out tongue) prior to extubation were 4 times more likely to require reintubation. 6 However, the study by Coplin et al reported similar extubation failure among brain injured subjects regardless of their Glasgow coma score. 23 In addition, using the Full Outline of UnResponsiveness (FOUR) score, which combines assessment of eyes, brainstem, reflexes, and respiration, to assess mental status in 62 subjects with a primary neurologic injury, Ko and colleagues reported similar scores among those who were successfully extubated and those that failed.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…5 The mortality of these SEE THE RELATED EDITORIAL ON PAGE 1050 patients is significantly higher than the mortality of patients who tolerate extubation, [5][6][7][8] so it is desirable to accurately identify patients who are at risk for re-intubation. [9][10][11][12][13][14] Some of the variability in the rate of extubation failure is probably due to differences in cohort characteristics, yet differences in physician practice may also explain some of this variation. 5 In particular, physicians may rely on different sets of variables, interpret variables with certain biases, or make different tradeoffs (in the case of extubation, between prolonged intubation and failed extubation).…”
Section: Introductionmentioning
confidence: 99%
“…(Demling et al, 1988;Engoren et al, 1999;Rady et al, 1999). Outras pesquisas com populações mistas estimaram uma freqüência que variou de 12 a 20% (Capdevilla et al, 1995;Epstein et al, 1997;Vallverdú et al, 1998;Khamiees et al, 2001;Esteban et al, 2002;Martinez et al, 3003;Salam et al, 2004;Seymour et al, 2004). Os estudos de pacientes neurológicos apresentam taxas bem distintas (Coplin et al, 2000;Namen et al, 2001 Outro fator avaliado por Namen et al (2001) A falência do desmame também tem sido associada à maior duração da ventilação mecânica (Torres et al, 1995), maior duração de internação hospitalar e em UTI (Torres et al, 1995;Perren et al, 2002;de Lassence et al, 2002, Fernandez et al, 2004Seymour et al, 2004) e maior taxa de traqueostomia (Epstein, 2003 …”
Section: A Falência Do Desmameunclassified